2009
DOI: 10.1002/stem.123
|View full text |Cite
|
Sign up to set email alerts
|

Ionizing Radiation Induces Ataxia Telangiectasia Mutated-Dependent Checkpoint Signaling and G2 But Not G1 Cell Cycle Arrest in Pluripotent Human Embryonic Stem Cells

Abstract: Human embryonic stem (ES) cells are highly sensitive to environmental insults including DNA damaging agents, responding with high levels of apoptosis. In order to understand the response of human ES cells to DNA damage, we investigated the function of the ataxia telangiectasia mutated (ATM) DNA damage signaling pathway in response to γ-irradiation. Here we demonstrate for the first time in human ES cells that ATM kinase is phosphorylated and properly localized to the sites of DNA double strand breaks within 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
168
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(193 citation statements)
references
References 48 publications
25
168
0
Order By: Relevance
“…Recent publications have suggested that hESC possess functional G1 and G2 checkpoints that are activated by DNA damage [16,34] and that may operate by downregulation of CDK2, but further study of this mechanism was needed. We have investigated this question in more detail and made the observations summarized as follows: (a) the G1 checkpoint is activated in hESC in response to CDK2 downregulation; (b) activation of the G1 checkpoint under these conditions results in phosphorylation of ATM and CHK2 and induces both the rapid (degradation of CDC25A) and slow response (p53 and p21 activation) as well as the activation of p38 MAPK and p27; (c) G1 checkpoint activation is an upstream event that forces hESC stalling in G1 in response to CDK2 downregulation; (d) activation of the p53 and p21 axis is not perturbed in the absence of CDK2; (e) CDK2 downregulation results in almost complete block of replication; (f) downregulation of CDK2 results in more extensive DNA damage although it does not stop the formation of DNA repair foci and activation of key factors involved in DNA repair; (g) downregulation of CDK2 results in increased apoptosis at the early time points after siRNA transfection, possibly to protect genomic stability whereas the checkpoint activation is taking place and enabling activation of the DNA repair machinery, although not sufficiently enough to clear the damage (these data are summarized in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recent publications have suggested that hESC possess functional G1 and G2 checkpoints that are activated by DNA damage [16,34] and that may operate by downregulation of CDK2, but further study of this mechanism was needed. We have investigated this question in more detail and made the observations summarized as follows: (a) the G1 checkpoint is activated in hESC in response to CDK2 downregulation; (b) activation of the G1 checkpoint under these conditions results in phosphorylation of ATM and CHK2 and induces both the rapid (degradation of CDC25A) and slow response (p53 and p21 activation) as well as the activation of p38 MAPK and p27; (c) G1 checkpoint activation is an upstream event that forces hESC stalling in G1 in response to CDK2 downregulation; (d) activation of the p53 and p21 axis is not perturbed in the absence of CDK2; (e) CDK2 downregulation results in almost complete block of replication; (f) downregulation of CDK2 results in more extensive DNA damage although it does not stop the formation of DNA repair foci and activation of key factors involved in DNA repair; (g) downregulation of CDK2 results in increased apoptosis at the early time points after siRNA transfection, possibly to protect genomic stability whereas the checkpoint activation is taking place and enabling activation of the DNA repair machinery, although not sufficiently enough to clear the damage (these data are summarized in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The function of p53-p21 axis has been studied by several groups in both mouse and human ESCs and in pluripotent human embryonal carcinoma cells using various strategies [10,[29][30][31][32]. Surprisingly, there have been many discrepancies between their findings, including differences in the ability of cells to transactivate the p21 gene or to produce increased levels of p21 protein when p21 transcripts are upregulated [10,[29][30][31]33]. When we examined p53 expression in hESCs with UVC-induced G1 delay, we found that at 3 hours after UVC irradiation, p53 protein is already dramatically increased, is phosphorylated on serines 15, 33, and 392, and localizes completely to cell nuclei.…”
Section: For the Experimental Design) (D-f)mentioning
confidence: 99%
“…The dominance of HR in ESCs is in contrast to somatic cells in which NHEJ is the dominant DNA DSB repair pathway and is possibly due to the large portion of time that these cells spend in S and G2 phase of the cell cycle when there is a template available for HR repair. Also, in contrast to somatic cells, IR induces predominantly G2 arrest in ESCs compared to G1 dominance in somatic 21/31 cells [71]. Additionally, the authors showed that in ESCs, γH2AX foci, an established marker of DNA DSBs [108], colocalised with both RAD51 and Ku70, indicating that both HR and NHEJ were playing a role.…”
Section: /31mentioning
confidence: 95%
“…In human ESCs a temporary G2/M (but not G1) arrest was observed 8 to 24 hours after irradiation with 2 Gy. This effect was shown to be dependent on ATM, a critical component of the DNA damage signalling pathway [71]. Wilson and co-workers (2010) resulted in a dose dependent reduction of embryoid body diameter [75].…”
Section: Effects Of Moderate Doses (05-5 Gy) Irradiation On Normal Smentioning
confidence: 98%